A new species of basal rhynchosaur (Diapsida: Archosauromorpha) from the early Middle Triassic of South Africa, and the early evolution of Rhynchosauria. (23rd June 2015) - Butler, Richard J.; Ezcurra, Martín D.; Montefeltro, Felipe C.; Samathi, Adun; Sobral, Gabriela
<x xml:space="preserve">Abstract</x> Rhynchosauria was an important clade of herbivorous archosauromorph reptiles during the Triassic, with a worldwide distribution. We describe a new genus and species of early rhynchosaur, Eohyosaurus wolvaardti gen. et sp. nov., from the early Middle Triassic (early Anisian) Cynognathus Assemblage Zone (Subzone B) of the Karoo Supergroup, South Africa. Eohyosaurus wolvaardti is known from a single skull, and is recovered as the sister taxon of Rhynchosauridae in a new phylogenetic analysis. Cynognathus Subzone B has previously yielded the stratigraphically oldest well‐understood rhynchosaur species, Mesosuchus browni and Howesia browni. Eohyosaurus wolvaardti increases the rhynchosaur diversity within this stratigraphical horizon to three species. Intriguingly, all currently confirmed rhynchosaur occurrences from the Early Triassic to earliest Middle Triassic are from South Africa. This may suggest a relatively restricted palaeogeographical distribution for early rhynchosaurs, followed by a global dispersal of rhynchosaurids during the Middle Triassic. © 2015 The Linnean Society of London